Undiagnosed Diabetes Mellitus and Its Predictors Among Socially Marginalized Menja Communities in Southwest Ethiopia - Assefa, Ashenafi; Shifera, Nigusie (Frontiers in Public Health, 2022)
Background: Diabetes mellitus (DM) is a metabolic disorder marked by a persistent high blood glucose level over a prolonged period of time linked to either the defects in insulin secretion, insulin action, or both. It is responsible for 537 million adults’ cases and 6.7 million deaths in 2021. However, about half of diabetics go undiagnosed. Low income and socially disadvantaged communities are the most vulnerable to the disease. Despite this fact nothing has been done among these communities, so this study aimed to assess the extent of undiagnosed diabetes and its predictors among socially marginalized Menja communities of south-west Ethiopia, 2021. Methods: A community-based study was done in Menja communities from April to June/2021. Sample size was calculated using the Single population proportion formula and systematic sampling technique were employed to select the households. Data were collected through face-to-face interviews utilizing an interviewer administered questionnaire to collect socio-demographic and behavioural characteristics, and anthropometric measurements were taken from each participant. Diabetes was defined as participants who had an FBG ⩾126 mg/dL or RBG >200 mg/dL. The multivariate logistic regression model was used to identify the predictors of diabetes; adjusted OR with a 95% CI was computed to assess the strength of associations. Results: The prevalence of undiagnosed diabetic mellitus among socially marginalized Menja communities was 14.7% [95% CI: (11.1-18.3)], and sex-specific prevalence was 16.8%, and 11.1% for males and female respectively. Factors; drank alcohol (AOR=3.0, 95% CI 1.49 to 6.05), family history of diabetic mellitus 4.4 (AOR=4.37, 95% CI 2.04 to 9.35), fewer vegetable consumption 3.5 (1.19-10.31) (AOR=3.5, 95% CI 1.19 to 10.31), low habit of physical exercise 3.3 (AOR=3.34, 95% CI 1.61 to 6.90) were the independent predictors of diabetes among Menja communities. Conclusion and Recommendations: Undiagnosed diabetes was high as compared to other settings. Alcohol use, family history of diabetes, vegetable consumption, and physical exercise were predictors of diabetes. Hence, the study suggests frequent screening and treatment are recommended for high risk groups. Minimizing alcohol drinking, frequent vegetable consumption and physical exercises were recommended measures for prevention and control of diabetes mellitus among the population of Ethiopia.